Organisational and environmental characteristics of residential aged care units providing highly person-centred care: a cross sectional study - Karin Sjögren; Marie Lindkvist; Per-Olof Sandman; Karin Zingmark; David Edvardsson (BMC, 2017)
Abstract Background Few studies have empirically investigated factors that define residential aged care units that are perceived as being highly person-centred. The purpose of this study was to explore factors characterising residential aged care units perceived as being highly person-centred, with a focus on organisational and environmental variables, as well as residents' and staff' characteristics. Methods A cross-sectional design was used. Residents (n = 1460) and staff (n = 1213) data from 151 residential care units were collected, as well as data relating to characteristics of the organisation and environment, and data measuring degree of person-centred care. Participating staff provided self-reported data and conducted proxy ratings on residents. Descriptive and comparative statistics, independent samples t-test, Chi2 test, Eta Squared and Phi coefficient were used to analyse data. Results Highly person-centred residential aged care units were characterized by having a shared philosophy of care, a satisfactory leadership, interdisciplinary collaboration and social support from colleagues and leaders, a dementia-friendly physical environment, staff having time to spend with residents, and a smaller unit size. Residential aged care units with higher levels of person-centred care had a higher proportion of staff with continuing education in dementia care, and a higher proportion of staff receiving regular supervision, compared to units with lower levels of person-centred care. Conclusions It is important to target organisational and environmental factors, such as a shared philosophy of care, staff use of time, the physical environment, interdisciplinary support, and support from leaders and colleagues, to improve person-centred care in residential care units. Managers and leaders seeking to facilitate person-centred care in daily practice need to consider their own role in supporting, encouraging, and supervising staff.